Malaysian mosques internal design considerations: a systematic literature review - Ahsani, Majid (Human Resource Management Academic Research Society (HRMARS), 2025)
Mosques should represent a connection between prayer and God, this symbolization should be reflected in the exterior and interior design. Malaysian mosques characterise a variety of styles, from small traditional structures to massive landmark complexes. While there are more than 5000 mosques in Malaysia, there is not enough literature on the mosque architecture in Malaysia. By utilizing systematic literature review method, this research investigates the related resources discussing the internal spaces of mosques in Malaysia and puts together the extracted information as a framework for planners and designers to gain a better understanding of the users’ needs before designing. The first objective is to explore the standards and design considerations for mosque design in general. Secondly, this paper is looking to discover design considerations for Malaysian mosques in particular. Later, by examining existing literature, considerations for physical, technical, and psychological aspects are extracted. Finally, suggestions on further investigation are made.